ANALISIS ARUS KAS SEBAGAI ALAT PERTIMBANGAN DALAM PENGAMBILAN KEPUTUSAN MANAJEMEN PADA PT. CARMA WIRA JATIM – PASURUAN - Yufenti Oktafiah; Eva Mufidah; Himmatul Aliya (Jurnal Inovasi Penelitian, 2023)
Cash is a company asset that is easy to liquidate, cash is included in the category of current assets and is easy to use for its financial operations. An overview of the company's cash condition is a function of the preparation of cash flow statements, which provide information about the company's collection and disbursement of cash. Cash flow is categorized into 3 parts, namely. operating activities, investing activities, and financing activities. All three contain different information and serve as a complement to one another in the main operations of the company. This study used a descriptive quantitative approach and took secondary data from the financial statements of PT. Carma Wira East Java 2019–2021. Data collection techniques used are field research and library research. The ratio analysis approach is used in cash flow analysis to describe future cash capabilities and explain existing cash capabilities. The results of this study from each of the cash flow ratio analysis methods used show that PT. Carma Wira Jatim only relies on funds from operating activities to support its operations, and the company is in unfavorable condition, as evidenced by the results of the analysis which tend to be low and have decreased every year.